Mineralogy and petrology of some granite rocks in the Canadian Shield north of Fort Chipewyan, Alberta - Klewchuk, P. (University of Calgary, 1972)
Bibliography: p. 126-134. This title is not available online. Access options are: - consulting the copy from Archives in our reading room in person - https://asc.ucalgary.ca/visiting/ - borrowing a circulating copy from the Library catalogue – https://ucalgary.primo.exlibrisgroup.com/discovery/search?vid=01UCALG_INST:UCALGARY&lang=en